1703 The Walking Thread – What Happens to Fistula-In-Ano Patients Who Are Lost to Follow Up? A Service Improvement Study. (12th October 2021) - Ellen, M; Wilson, B; Anderson, D
Abstract: Aim: 1/3 of idiopathic cryptoglandular abscesses can result in fistula-in-ano. Current practice is to incise and drain primary abscesses and safety net for patients to return as necessary. Known fistula patients will be appointed for Examination Under Anaesthetic at 6-12 weeks.Is this best management or do they become "elective emergencies"? Method: We performed a retrospective audit of management of fistula-in-ano over 4 years. We used a precollected data set of Cryptoglandular abscesses, excluding inflammatory, radiation or malignant causes and collected data for patients lost to follow up, including presentation, fistula diagnosed at first or subsequent attendance, number of operations, number of attendances and seton placement. Results: 512 patients were operated on for cryptoglandular abscess causing fistula-in-ano between 2013 and 2017. 10% (N = 50) were lost to follow up. 32 had documented follow up plans, that were not fulfilled (eg elective theatre not booked). Of these, 18 were elective attendances, 14 emergency. 24 of the 32 had a Seton sited prior to being lost to follow up Conclusions: The various presentations (emergency, elective, clinic or day surgery) and long waiting lists mean many of these patients are presenting as emergencies still awaiting follow up. Many are lost to follow-up, with Setons in situ. We propose a fortnightly hot-clinic system, registrar led to assess and manage these patients. This would provide an elective clinic to allow single point of access to fistula-in-ano patients ensuring prompt follow up and reduction in unnecessary EUA, as well as improving senior colorectal trainees exposure to perianal disease and its management.